Upaya Peningkatan Pengetahuan tentang Pendidikan Kesehatan Reproduksi dan Seksual pada Usia Remaja - Ida Baroroh (LPPM Akbid Harapan Ibu Pekalongan, 2021)
Reproductive Health is a condition of being physically, mentally and socially healthy as a whole, not only free from diseases or disabilities related to the reproductive system, function and process in men and women. Adolescence as the starting point of the reproductive process shows that the preparation of intervention strategies needs to start long before the fertile age period. The value of girls and boys in the family and society, and how they are treated are important factors that determine their future reproductive health. The aim of this community service is to increase youth knowledge about reproductive and sexual health education at adolescence. Methods of health education are (1) Socialization and Licensing, (2) Conducting Affirmations and Pre Tests (3) Conducting Adolescent Health Education on Reproductive and Sexual Health in Adolescents. (4) Evaluation of the results of health education activities with a Pre Test. The results of health education activities show good enthusiasm during the health education process. This enthusiasm was shown by the excellent response of the participants and the willingness of the participants to ask questions and describe their opinions. The results of this health education are expected to increase participants' knowledge and understanding of the importance of reproductive health and sexual health in adolescents. This is indicated by the results of the pre and post test questionnaires which show an increase in knowledge about reproductive and sexual health education .